Accelerated neural differentiation of mouse embryonic stem cells on aligned GYIGSR-functionalized nanofibers. (15th July 2018) - Silantyeva, Elena A.; Nasir, Wafaa; Carpenter, Jacqueline; Manahan, Olivia; Becker, Matthew L.; Willits, Rebecca K.
Graphical abstract: Abstract: Substrates for embryonic stem cell culture are typified by poorly defined xenogenic, whole proteins or cellular components that are difficult and expensive to generate, characterize, and recapitulate. Herein, the generation of well-defined scaffolds of Gly-Tyr-Ile-Gly-Ser-Arg (GYIGSR) peptide-functionalized poly( ε -caprolactone) (PCL) aligned nanofibers are used to accelerate the neural lineage commitment and differentiation of D3 mouse embryonic stem cells (mESCs). Gene expression trends and immunocytochemistry analysis were similar to laminin-coated glass, and indicated an earlier differentiation progression than D3 mESCs on laminin. Further, GYIGSR-functionalized nanofiber substrates yielded an increased gene expression of Sox1, a neural progenitor cell marker, and Tubb3, Cdh2, Syp, neuronal cell markers, at early time points. In addition, guidance of neurites was found to parallel the fiber direction. We demonstrate the fabrication of a well-defined, xeno-free functional nanofiber scaffold and demonstrates its use as a surrogate for xenogenic and complex matrixes currently used for the neural differentiation of stem cells ex vivo . Statement of Significance: In this paper, we report the use of GYIGSR-functionalized poly( ε -caprolactone) aligned nanofibers as a tool to accelerate the neural lineage commitment and differentiation of D3 mouse embryonic stem cells. The results indicate that functional nanofiber substrates promote faster differentiation than laminin coated substrates. The data suggest that aligned nanofibers and post-electrospinning surface modification with bioactive species can be combined to produce translationally relevant xeno-free substrates for stem cell therapy. Future development efforts are focused on additional bioactive species that are able to function as surrogates for other xenogenic factors found in differentiation media.